The authority in the Church: original key to understand the present situation of the Anglican-Roman Catholic relations - Martínez Oliveras, CMF, Carlos (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2017)
The unilateral decisions taken by certain sectors of the Communion have led the Anglicanism to a very difficult situation. It is a symptom of a deeper question: how to understand the theological meaning of the authority in the Church and its exercise. In the bilateral theological dialogue between Anglicans and Roman Catholics authority has been always a central question. The different understanding is rooted in the moment of breaking-off. This paper studies the historical events wich led to the break of the communion between Canterbury and Rome using a specific point of view: the perception of the authority in the Church. Beyond of temporary factors, the new understanding wich comes up in the XVIth century and its ecclesiological consequences caused a schism that has marked the life of the Church until now. The future of the relation between the Catholic Church and the Anglican Communion depends on the capacity to reach an agreement on this matter.
Keywords: anglicanism; authority; communion; primate; Church; Henry VIII